PERBEDAAN TINGKAT PENGETAHUAN TENTANG KEHAMILAN SEHAT DENGAN INDIKATOR KESEHATAN IBU HAMIL YANG MENGIKUTI KELAS IBU HAMIL - Yuniarsih, Sri Mumpuni; Indriono, Anik; Widhowati, Siwi Sri (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: Maternal Mortality Rate (MMR) in Indonesia is still one of the highest in Southeast Asia (ASEAN). World Health Organization (WHO) as the international organization is targeting a decrease in the (MMR) as one of the targets in the achievement of the Millennium Development Goals (MDGs). However, based on the evaluation of part-time Development Plan 2010-2014, the target of reducing maternal mortality rate in Indonesia is still very difficult to achieve. One of the government's efforts to accelerate the decline of maternal mortality rate is a mother class program. Objective: This study aimed to analyze the achievement of the indicators of maternal health program in comparison with the class of pregnant women who do not attend pregnant women class. Methods: This research was a quantitative research with cross sectional design that compared the achievement of the nine indicators of the health of pregnant women in the two groups of pregnant women. The variable in this study was a comparison of weight gain, blood pressure, upper arm circumference (MUAC), high fundus, fetal heart rate (FHR), the consumption of iron tablets, hemoglobin levels, antenatal visits, and knowledge about healthy pregnancies. The number of samples in this study were 209 respondents which were divided into groups of 86 respondents in a class of pregnant women and 123 respondents in the non-class group of pregnant women. Chi square and t test was used to analyze the comparison of maternal health indicators achievement advance of two groups of respondents. Results and Discussion: The results showed that there were significant difference in knowledge about a healthy pregnancy, the consumption of iron tablet and number of antenatal visits. Pregnant women who attended classes had a better knowledge, more Fe tablet consumption and ANC visit. While indicators of weight gain, MUAC, TFU and DJJ of all respondents were within the normal range according to gestational age when the data retrieval. The other indicators such as hemoglobin level, systolic and diastolic blood pressure did not reveal any significant differences between the two groups of respondents.   Keywords: Mother class program; maternal health indicators